2010
DOI: 10.5194/acpd-10-6279-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brown carbon in tar balls from smoldering biomass combustion

Abstract: Abstract. We report the direct observation of large-scale production of spherical, carbonaceous particles – "tar balls" – from smoldering combustion of two commonly occurring dry mid-latitude fuels. Real-time measurements indicate that brown carbon is an important component of tar balls. The spectrum of the imaginary parts of their complex refractive indices can be described with a Lorentzian-like model with an effective resonance wavelength in the ultraviolet (UV) spectral region. Sensitivity calculations for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
120
4
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(138 citation statements)
references
References 41 publications
(25 reference statements)
13
120
4
1
Order By: Relevance
“…However, this approach has been recently challenged by mounting observational evidence of carbonaceous aerosol exhibiting a strong absorption in the near ultra-violet wavelengths of the shortwave spectrum with an AǺE41 [2,[9][10][11][12]. This increased absorption at shorter visible wavelengths has been attributed to a class of near-UV light absorbing OC aerosols (hereafter referred to as light-absorbing OC or LAOC) [13].…”
Section: Introductionmentioning
confidence: 98%
“…However, this approach has been recently challenged by mounting observational evidence of carbonaceous aerosol exhibiting a strong absorption in the near ultra-violet wavelengths of the shortwave spectrum with an AǺE41 [2,[9][10][11][12]. This increased absorption at shorter visible wavelengths has been attributed to a class of near-UV light absorbing OC aerosols (hereafter referred to as light-absorbing OC or LAOC) [13].…”
Section: Introductionmentioning
confidence: 98%
“…Recently Ueda et al [28] classified soot-containing particles into five major types: soot aggregates, dome-shaped particles, particles having satellite structures, single nearly spheroidal particles, and clusters of spheroidal units. R.K. Chakrabarty et al (private communication) have conducted a literature survey and identified three major biomass burning aerosol habits: fractal soot aggregates, individual and semi-externally mixed tar balls [25], and carbonaceous super-aggregates [30] (we use the definitions of external, semi-external, and internal mixtures of particles according to Ref. [44]).…”
Section: Introductionmentioning
confidence: 99%
“…They can also limit atmospheric visibility and have a highly negative effect on human health [12]. Owing to the notoriously complex morphology of such particles [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], theoretical modeling of their scattering and absorption properties is a highly nontrivial task and has often been based on approximate approaches with poorly defined accuracy and range of applicability. However, the growing need for much improved knowledge of BC and BC-containing aerosols and their climatic, ecological, and visibility effects imposes strict limitations on quantitative uncertainties in particle scattering and absorption properties entering optical characterization and remote sensing applications as well as atmospheric radiation budget computations [31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the effect of different sulfate coatings on absorption enhancement was investigated using this method. Briefly, the model utilized a volume equivalent diameter of 132.7 nm estimated from the effective density and OC fraction, a complex refractive index of 2.0 þ 0.2i for the BC-BrC core retrieved from Mie "closure" calculations using measured absorption and scattering coefficients (Chakrabarty et al, 2010), and the complex refractive indices of sulfates coating according to the volume weighted mixing rule (see more details in SI).…”
Section: Mie Theory Calculation With a Core-shell Configurationmentioning
confidence: 99%
“…Condensable organic species produced from either biomass burning (Lewis et al, 2008) or diffusion flames (Schnaiter et al, 2006), characterized by absorption in the visible light range with an absorption Ångstr€ om exponent (AAE) greater than unity, has been linked to the source of BrC. The presence of both BC and BrC in particulate matters formed from biomass/biofuel burning at flaming and smoldering conditions complicates the estimation of their climate impacts (Chakrabarty et al, 2010;Kirchstetter et al, 2004;Lack et al, 2012).…”
Section: Introductionmentioning
confidence: 99%